GARZAN NEHRİ HAVZASI'NDA ENTEGRE SÜRDÜRÜLEBİLİR SU YÖNETİMİ: YAĞMUR SUYU HASADI, GRİ SU GERİ DÖNÜŞÜMÜ VE LEED KRİTERLERİ UYGULAMASI - BARS, BURCU ŞEŞEOĞULLARI (Fırat Üniveristesi, 2025)
Bu çalışma, Garzan Nehri havzasının yarı kurak iklim koşullarında yaz aylarında ortaya çıkan ciddi su kıtlığı ile ilkbahar dönemindeki ani yağışların yol açtığı taşkın ve kanalizasyon yükü risklerini ele almıştır. Öncelikle 2000–2024 dönemine ait meteorolojik veriler kullanılarak bölgedeki yıllık yağış rejiminin mevsimsel düzensizlikleri nicelendirildi; yıllık ortalama 800 mm yağışın büyük bölümü Ocak–Mayıs aylarında düşerken Haziran–Ağustos'ta neredeyse kuraklık oluştuğu ve yıllık toplamın 592–1 739 mm arasında dalgalandığı gösterildi. Bu veriler ışığında, proje sahası olarak seçilen 1 000 m² çatı ile 500 m² otopark alanından, %85 verimlilikle yıllık 1 020 m³ yağmur suyu hasadı potansiyeli hesaplandı; ayrıca, literatürde günlük kişi başı 100 L gri su üretimi ve %15 kayıp varsayımlarıyla 300 m³/yıl kullanılabilir gri su, düşük debili armatür ve sensörlü sistemlerle de ek 100 m³/yıl tasarruf öngörüldü. Toplam 1 420 m³/yıl su tasarrufu, yıllık 2,5 $/m³ birim su maliyeti esas alınarak 3 550 $/yıl tasarruf sağlarken, 50 000 $ kurulum ve 2 000 $/yıl bakım maliyetleri dikkate alındığında kombine senaryonun net fayda ve geri ödeme süresi analizlerinde 32 yıl gibi makul bir performans sunduğu belirlendi. Son olarak, önerilen entegre su yönetimi sisteminin LEED sertifikasyonunda Rainwater Management (2 puan), Water Use Reduction (3 puan), Innovation in Design (1 puan) ve Measurement & Verification (1 puan) kredilerine uygun olduğu vurgulanarak proje tasarımının hem ekolojik dayanıklılığı hem de sertifikasyon gereksinimlerini karşılayacak bütüncül bir çözüm sunduğu ortaya konmuştur.

This study addresses the severe water scarcity experienced during the summer months and the flood and sewage overload risks caused by sudden springtime rainfall in the semi-arid climate of the Garzan River basin. First, meteorological data from 2000–2024 were analyzed to quantify the seasonal irregularities of the annual precipitation regime: although the basin receives an average of 800 mm of rainfall per year, most of it falls between January and May, while June through August approaches drought conditions, and annual totals fluctuate between 592 mm and 1 739 mm. Based on these findings, a catchment area of 1 000 m² of roofing and 500 m² of parking surface was selected for the project, and a rainwater harvesting potential of 1 020 m³ per year was calculated assuming 85 % system efficiency. In addition, literature-based estimates of 100 L per person per day of greywater production with a 15 % system loss yielded an available greywater volume of 300 m³ per year, and low-flow fixtures and sensor-activated systems were projected to save an additional 100 m³ per year. With a total annual water savings of 1 420 m³ and a unit water cost of $2.50 /m³, the project would save $3 550 per year. Considering a capital cost of $50 000 and annual maintenance of $2 000, the combined scenario achieves a reasonable payback period of approximately 32 years. Finally, it was demonstrated that the proposed integrated water management system is well-suited to LEED certification, offering credits in Rainwater Management (2 points), Water Use Reduction (3 points), Innovation in Design (1 point), and Measurement & Verification (1 point), thus providing a holistic solution that meets both ecological resilience and sustainability certification requirements.
Integrated sustainable water management in the Garzan River Basin: Rainwater harvesting, greywater recycling and LEED criteria application
Keywords: İnşaat Mühendisliği